Agroforestri Kelapa Sawit Sekala Kecil di Jambi dan Kalimantan Tengah: Hambatan dan Faktor-faktor yang Mempengaruhi Adopsi - Ari Susanti; Hero Marhaento; Dwiko Budi Permadi; Budiadi Budiadi; Muhammad Ali Imron; Hermudananto Hermudananto; Handojo Hadi Nurjanto; Denni Susanto; Heri Santoso; Irfan Bakhtiar; Siti Maimunah (Jurnal Ilmu Kehutanan, 2021)
Oil palm has become an important export commodity for Indonesia and has been cultivated by both smallholders and large scale companies mainly as monoculture plantations. Research suggests that this massive monoculture practice has led to adverse impacts on natural and social systems. Smallholders encounter difficulties to cope with extreme climate events such as long dry seasons, fluctuating commodity price and long-term tenure insecurity. We argue that oil palm agroforestry (OPAF) could become a promising and realistic alternative to deal with these problems under social forestry (SF) program. To date, OPAF has been adopted by merely small number of smallholders in Indonesia in a limited scale. This article aims at analysing the barriers and factors which influence the decision of smallholders in adopting OPAF. We employ a hybrid method which combines qualitative and quantitative analysis. Binary logistic regression models were constructed to identify factors influencing OPAF adoption. Our findings suggest that education, having side job and relative location of smallholders’ have significantly influenced smallholders’ decision in adopting OPAF. Knowledge gaps especially on the yields and management of OPAF have likely led to low OPAF adoption.